Muslim-Malay Women in Political Leadership: Navigating Challenges and Shaping the Future - Ramli, Mohd Anuar; Syed Jaafar, Syed Mohd Jeffri; Md Ariffin, Mohd Farhan; Kasa, Annuar Ramadhon; Qotadah, Hudzaifah Achmad; Achmad, Adang Darmawan; Siswanto, Siswanto (Fakultas Syariah UINSI Samarinda, 2024)
Women's participation in politics, particularly in leadership roles, remains a contentious topic within Muslim communities. This situation is due primarily to the prevalent interpretation that men are inherently more qualified for national leadership positions, as influenced by the patriarchal structure of society and persistent stereotypes that undermine women's capabilities. These cultural and societal barriers hinder women's ascension to the highest echelons of political power, especially in countries like Malaysia and Indonesia. This study seeks to analyze Islamic jurisprudence originating from the Quran and hadith interpretation of women's status to address the common misconception that Islam inherently supports misogyny. It then contextually puts the analysis of Malay women's obstacles in achieving political leadership in Malaysia and Indonesia. This socio-legal research is aimed at understanding the complexities of gender-based challenges in political settings caused by prevailing non-moderate interpretation of Sharia sources combined with patriarchal culture in the Malay world. It reveals that historically, in Malay, women have been entrusted with national leadership responsibilities. Similarly, from an Islamic perspective, there appears to be a misinterpretation of hadith regarding the prohibition of appointing women as national leaders. Thus, this traditional culture that permits women to hold leadership positions must be re-polished because women can utilize their liberties, including leadership, previously denied by non-moderate views.